Leadership styles and their relationship with motivation in high school teams - Quintal Marín , Ivette Alejandrina (Consorcio de Universidades Mexicanas A.C., 2015)
This research had the target to analyze students leadership perception toward their own leader team, who also was selected by them, and their relation in high school students from two UADY affiliated schools. It is considered analyze teamwork in an educational context because it is one of the most used tools in this environment. It was an empirical, quantitative, transversal and field research, made in an educational context with 69 participants. The two instruments used were: Kurt Lewin leadership test, which identifies three kind of leadership: authoritarian, democratic and laissez-faire; and the motivations scale EM1, based on the McClelland model by Álvarez, which identifies three motivational types: power, achievement and affiliation. The results evidence show that the most frequently perception was toward the leader with democratic style, with a positive correlation of power motivation. This leadership style makes feel the members fundamental encouraging their participation to achieve their goal, therefore this relationship results congruent with theory, because the principal stimulation to people with this motivation is that they are important to the team. It is expected that the work contributes providing information for future research on the academic area to create strategies for increasing student motivation.